Deuterium metabolic imaging in the human brain at 9.4 Tesla with high spatial and temporal resolution - Ruhm, Loreen; Avdievich, Nikolai; Ziegs, Theresia; Nagel, Armin M.; De Feyter, Henk M.; de Graaf, Robin A.; Henning, Anke (NeuroImage (Orlando, Fla.), 2021)
To present first highly spatially resolved deuterium metabolic imaging (DMI) measurements of the human brain acquired with a dedicated coil design and a fast chemical shift imaging (CSI) sequence at an ultrahigh field strength of B0 = 9.4 T. 2H metabolic measurements with a temporal resolution of 10 min enabled the investigation of the glucose metabolism in healthy human subjects. The study was performed with a double-tuned coil with 10 TxRx channels for 1H and 8TxRx/2Rx channels for 2H and an Ernst angle 3D CSI sequence with a nominal spatial resolution of 2.97 ml and a temporal resolution of 10 min. The metabolism of [6,6′-2H2]-labeled glucose due to the TCA cycle could be made visible in high resolution metabolite images of deuterated water, glucose and Glx over the entire human brain. X-nuclei MRSI as DMI can highly benefit from ultrahigh field strength enabling higher temporal and spatial resolutions.